2015
DOI: 10.1080/13642987.2015.1032268
|View full text |Cite
|
Sign up to set email alerts
|

The religious freedom peace

Abstract: Around the world, religion's influence on societies and politics is increasing. Arguably religion is today a more salient feature of international politics than at any point in the last 300 years. Yet this increase in religion's prominence comes at the precise time that religious expression has come under unprecedented assault from both state actions and communal hostilities involving religion. At the same time, religious extremism and violence have also been on the rise globally. This article makes the case t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

5
5

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…According to this view, women should also be less draconian in their approach to dissent and less willing to use violence against their people (Ruddick 1989). This has the effect of removing a major motivation for terrorist activity, as past scholarship has shown that the excessive use of force by the state is a key source of mass grievance and an important driver of terrorist activity (Abrahms 2007; Regan and Norton 2005; Saiya 2015; Saiya and Scime 2015; Wimmer, Erik-Cederman, and Min 2009). Furthermore, women who are allowed to participate in policy development and implementation also have an important role to play by bringing their unique gender expertise to counterterrorism measures (United Nations General Assembly 2010).…”
Section: The Hillary Doctrine and Anti-american Terrorismmentioning
confidence: 99%
“…According to this view, women should also be less draconian in their approach to dissent and less willing to use violence against their people (Ruddick 1989). This has the effect of removing a major motivation for terrorist activity, as past scholarship has shown that the excessive use of force by the state is a key source of mass grievance and an important driver of terrorist activity (Abrahms 2007; Regan and Norton 2005; Saiya 2015; Saiya and Scime 2015; Wimmer, Erik-Cederman, and Min 2009). Furthermore, women who are allowed to participate in policy development and implementation also have an important role to play by bringing their unique gender expertise to counterterrorism measures (United Nations General Assembly 2010).…”
Section: The Hillary Doctrine and Anti-american Terrorismmentioning
confidence: 99%
“…Additionally, it highlights the important role political institutions play in shaping religious violence and religious politics more broadly. While religious beliefs matter, it is their political context that determines religion's impact on society and its form, whether violent or peaceful (Philpott 2007;Toft, Philpott, and Shah 2011;Saiya 2015Saiya , 2018Saiya and Scime 2015;Henne 2017;Saiya and Fidler 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in violent attacks against Christians can be understood as a response to religious conversion and the perceived inroads being made by Christians among marginalized Hindu groups. This argument is informed by a recent body of scholarship that has examined the effect of restrictions on religion on the production of violent conflict (Grim and Finke, 2011;Henne et al, 2012;Saiya, 2015Saiya, , 2017Saiya, , 2018Saiya, , 2019Toft et al, 2011). As argued in the following section, anti-conversion laws generate violent persecution against Christians by creating a culture of vigilantism and backlash in the states where they are enforced.…”
Section: Violent Christian Persecution In Indiamentioning
confidence: 99%